Risk of pneumonia and pneumococcal disease in people with severe mental illness: English record linkage studies. - Seminog, O; Goldacre, M (2013)
BACKGROUND: People with severe mental illness have a higher risk than others of some physical diseases. The risk of pneumococcal disease in people with mental disorders is unknown. This is potentially important because vaccines against the pneumococcus are available. METHODS: We used two datasets of linked hospital admission and death records, the Oxford Record Linkage Study and all-England linked Hospital Episode Statistics, to estimate the risk of lobar pneumonia and other pneumococcal disease (here, all collectively termed pneumococcal disease) in people hospitalised with schizophrenia, bipolar disorder, depression or anxiety. We compared rates of pneumococcal disease in each cohort with rates in a comparison cohort of people without a record of hospitalisation for these psychiatric disorders. FINDINGS: The risk of pneumococcal disease in each psychiatric group was significantly high in both datasets. In the English national dataset (spanning 1999-2011), the risk of pneumococcal disease in people hospitalised with schizophrenia, bipolar disorder, depression or anxiety was, respectively, 2.3 (95% CI 2.2 to 2.4), 2.3 (2.2 to 2.3), 2.1 (2.0 to 2.1) and 2.2 (2.1 to 2.2). The risk remained high for years after discharge, suggesting an association with the psychiatric disorder rather than with the event of hospitalisation. CONCLUSIONS: Severe mental illness is a risk factor for lobar pneumonia, pneumococcal pneumonia, pneumococcal septicaemia and meningitis. Possible explanations for the elevated risk include factors relating to lifestyle and health-risk activities. If our findings are replicated elsewhere, there would be a case for considering routine pneumococcal immunisation for people with severe mental illness.